HDAC Inhibition Suppresses Cardiac Hypertrophy and Fibrosis in DOCA-Salt Hypertensive Rats via Regulation of HDAC6/HDAC8 Enzyme Activity - Hae Jin Kee; Eun Hui Bae; Sangha Park; Ko Eun Lee; Sang Heon Suh; Soo Wan Kim; Myung Ho Jeong (Karger Publishers, 2013)
Background: Inhibition of histone deacetylase (HDAC) was reported to suppress cardiac hypertrophy and fibrosis in various hypertrophic animal models. However, the HDAC expression profile and HDAC enzyme activity have not yet been investigated in DOCA-salt hypertensive rats. Methods: Unilaterally nephrectomized rats were implanted with DOCA strips. DOCA-salt rats then received a control diet with vehicle or valproate. We measured the expression of cardiac hypertrophic markers, class I HDACs, class II HDACs, fibrosis, and HDAC enzyme activity. Results: Here we report that sodium valproate inhibits the cardiac hypertrophy accompanied by fibrosis in the heart of chronic hypertensive rats. We show that expression of GATA6 and HDAC6 is upregulated in DOCA-salt hypertension. In addition, HDAC6 and HDAC8 enzyme activity is attenuated by sodium valproate. Conclusion: These results suggest that a novel HDAC6- and HDAC8-selective inhibitor is needed to treat or prevent pathological cardiac hypertrophy.